BREEDING AND GROWING IN POND FISH FARMING (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article discusses such processes as breeding work carried out in pond fishing, the determination of productive breeds, the preparation of parent fish for the breeding season, certain environmental problems and the fishing industry. In pond fish farming, breeding work consists in how important it is and how urgent tasks are performed. New approaches implemented in this area are presented, as well as information on their environmental and economic importance.